(untitled) (International Journal of Natural Sciences, 2012)
Tuberculosis is a global public health issue and a disease burden in Africa and Asia. Bangladesh is one of the high burden countries in Southeast Asian region. Mycobacterium tuberculosis the causative agent of tuberculosis, is a devastating bacterium because it spreads person to person, acquired multiple antibiotic resistance and most importantly has the limitation in rapid diagnosis, specially in case of extrapulmonary infection. Here we showed Real-Time PCR assay with the primers targeting IS6110 is a better method than conventional AFB microscopy for the diagnosis of extrapulmonary tuberculosis. For the comparative study 99 extrapulmonary specimens from 9 different parts of the body were collected from suspected patients. Among those only 10 samples were positive, where 50% them were scanty positive in AFB microscopy, on the other hand 33 samples were positive in RealTime PCR assay. All samples positive in AFB microscopy were also positive in Real-Time PCR assay with an additional 23 positive. Higher percentage of positive results were found in Real-Time PCR analysis in all the samples except Percutaneous nephrostomy (PCN) fluid and Pus. The sharp differences in the result indicate the effectiveness and of the Real-Time PCR assay over the conventional AFB microscopy. High precision and accuracy make it better choice as a diagnostic method for the diagnosis of extrapulmonary tuberculosis. DOI: http://dx.doi.org/10.3329/ijns.v2i1.10880 International Journal of Natural Sciences (2012), 2(1): 26-32